A review of the surface heat transfer coefficients of radiant heating and cooling systems. (15th July 2019) - Shinoda, Jun; Kazanci, Ongun B.; Tanabe, Shin-ichi; Olesen, Bjarne W.
Abstract: Heat transfer coefficients are often used to describe the thermal behavior of radiant systems in buildings and how they transfer heat between their cooled/heated surfaces and the room. In addition to current standards, several studies have been conducted to determine such heat transfer coefficients by means of experiments and simulations. Inconsistency is evident in the values and expressions derived for this purpose. The present study investigated possible sources of discrepancy in an extensive literature review of articles, standards and guidelines that focus on the heat transfer coefficients of cooled/heated surfaces. Measurement data provided by different authors were analyzed to compare both the amount of heat transfer and the estimated heat transfer coefficients. These estimated values and expressions were used to predict the measured data reported in other articles, to examine their accuracy. Larger deviations and prediction errors were found in the total and convective heat transfer values than in radiant heat transfer, which had a range of errors within ±20% throughout the literature. The major sources of error were shown to be the calculation procedure for each heat transfer mechanism, the choice of reference temperature and its measurement height and position, and room dimensions. It is suggested that heat transfer coefficients should be chosen by matching the calculation/measurement conditions in which they were obtained to the purpose and conditions in which they will be applied. Highlights: Surface heat transfer coefficients are critical parameters for designing and evaluating performance of radiant systems. A literature review was conducted for the surface heat transfer coefficients of radiant systems. Measured heat transfer and the prediction accuracy of suggested heat transfer coefficients were compared. Measurement conditions and calculation methods were identified to be potential causes of discrepancies. Suggestions were made for future studies and how to select the appropriate heat transfer coefficient from literature.